Recent advances in nanotherapeutics for the treatment and prevention of acute kidney injury - Hui Yu; Di Liu; Gaofeng Shu; Feiyang Jin; Yongzhong Du (Elsevier, 2021)
Acute kidney injury (AKI) is a serious kidney disease without specific medications currently except for expensive dialysis treatment. Some potential drugs are limited due to their high hydrophobicity, poor in vivo stability, low bioavailability and possible adverse effects. Besides, kidney-targeted drugs are not common and small molecules are cleared too quickly to achieve effective drug concentrations in injured kidneys. These problems limit the development of pharmacological therapy for AKI. Nanotherapeutics based on nanotechnology have been proved to be an emerging and promising treatment strategy for AKI, which may solve the pharmacological therapy dilemma. More and more nanotherapeutics with different physicochemical properties are developed to efficiently deliver drugs, increase accumulation and control release of drugs in injury kidneys and also directly as effective antioxidants. Here, we discuss the recent nanotherapeutics applied in the treatment and prevention of AKI with improved effectiveness and few side effects.